2012
DOI: 10.3945/jn.112.161828
|View full text |Cite
|
Sign up to set email alerts
|

Status of Vitamins B-12 and B-6 but Not of Folate, Homocysteine, and the Methylenetetrahydrofolate Reductase C677T Polymorphism Are Associated with Impaired Cognition and Depression in Adults

Abstract: The C677T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene differs in frequency in various ethnic groups that have differing prevalence of age-related cognitive impairments. We used a series of neuro-psychological tests to examine the association of the MTHFR C677T polymorphism with cognition and depression and also to assess whether genotype modifies the association of folate and homocysteine with these outcomes. This study analyzed pooled cross-sectional data from 2 ethnically diverse coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 66 publications
0
55
0
2
Order By: Relevance
“…Other investigations on the relationship between nutrients and depression have demonstrated a role of folate (Farah, 2009, Gilbody et al, 2007, Morris et al, 2008, tryptophan (Cowen et al, 1989, DeMyer et al, 1981, Maes et al, 1987, zinc (Cope and Levenson, 2010, Szewczyk et al, 2011, iron (Maes et al, 1996, Stewart and Hirani, 2012, Vahdat Shariatpanaahi et al, 2007, Yi et al, 2011, CoQ10 (Maes et al, 2009b), vitamin B6 (Merete et al, 2008, Moorthy et al, 2012, Skarupski et al, 2010, Williams et al, 2005, vitamin B12 (Hintikka et al, 2003, Moorthy et al, 2012, and selenium (Gao et al, 2012, Mokhber et al, 2011, Pasco et al, 2012. However, findings on most of these nutrients require further investigation before definitive conclusions about their relationship with depression can be made.…”
Section: The Relationship Between Diet and Depressionmentioning
confidence: 99%
“…Other investigations on the relationship between nutrients and depression have demonstrated a role of folate (Farah, 2009, Gilbody et al, 2007, Morris et al, 2008, tryptophan (Cowen et al, 1989, DeMyer et al, 1981, Maes et al, 1987, zinc (Cope and Levenson, 2010, Szewczyk et al, 2011, iron (Maes et al, 1996, Stewart and Hirani, 2012, Vahdat Shariatpanaahi et al, 2007, Yi et al, 2011, CoQ10 (Maes et al, 2009b), vitamin B6 (Merete et al, 2008, Moorthy et al, 2012, Skarupski et al, 2010, Williams et al, 2005, vitamin B12 (Hintikka et al, 2003, Moorthy et al, 2012, and selenium (Gao et al, 2012, Mokhber et al, 2011, Pasco et al, 2012. However, findings on most of these nutrients require further investigation before definitive conclusions about their relationship with depression can be made.…”
Section: The Relationship Between Diet and Depressionmentioning
confidence: 99%
“…Indeed, a review by Smith (41) some years ago reported that 90 out of 100 published cross-sectional and prospective studies showed a link between elevated homocysteine and/or low B-vitamins concentrations with cognitive dysfunction. Most of these studies have focused on elevated plasma homocysteine concentrations (42)(43)(44)(45)(46) , and/or a combination of suboptimal status of folate and vitamin B 12 (47)(48)(49)(50)(51)(52)(53)(54) and to a much lesser extent on vitamin B 6 ( 55,56) . To the authors' knowledge, no published study thus far has focused on riboflavin alone as a potential contributor to cognitive health.…”
Section: Evidence Linking B-vitamins With Brain Health In Ageingmentioning
confidence: 99%
“…zwracają uwagę na fakt, że niski poziom witaminy B 12 był skojarzony z gorszymi wynikami w teście MMSE (Mini Mental State Examination) oraz z więk-szym ryzykiem wystąpienia depresji u starszych osób. Przeciwnie natomiast w tych badaniach nie stwierdzono, aby foliany i homocysteina miały wpływ na funkcje poznawcze i poziom depresji [20].…”
Section: Dyskusjaunclassified